Wadawurrung Dya Baap Ngobeeyt: teaching spatial mapping technologies. Issue 4 (2014) - ,; ,; ,
Abstract : Purpose – Aboriginal communities in Australia must have mapping information and technology to effectively and independently administer their land holdings and to define, evidence and thus protect their community and cultural identity. The purpose of this paper is to report on a pilot project that developed a customisable education programme to support Indigenous communities in the uptake of spatial mapping technologies to protect and manage cultural heritage in Victoria, Australia.Design/methodology/approach – A training programme to support Wadawurrung capabilities in spatial mapping technologies was developed, delivered and evaluated. Concurrently, the system's database was indigenised by Wadawurrung cultural heritage workers. Types and numbers of culturally significant sites mapped using the technologies were collated. The impact of the training and technologies for students and the Wadawurrung community was gauged through participation levels and evaluations. The approach to indigenous spatial mapping projects is informed by postcolonial theories interrogating neo‐colonialist cartographic practices.Findings – Indigenous communities need to be resourced in the uptake of spatial mapping technologies and if universities are going to be involved in co‐developing positive learning experiences that encourage the uptake of the technologies, they must have appropriate and respectful relationships with Aboriginal communities. Training programmes need to accommodate learners with diverse educational experiences and technological wherewithal.Research limitations/implications – Findings from the training evaluations are based on a small number of participants; however, they seem to be supported by literature.Practical implications – The education model developed is customisable for any Indigenous community in Australia.Social implications – The social and political importance of spatial mapping technologies for Indigenous Australians is evident as is the need for educational providers to have appropriate and respectful relationships with Aboriginal communities to co‐develop positive learning experiences that encourage the uptake of the technologies.Originality/value – The Wadawurrung Dya Baap Ngobeeyt Cultural Heritage Mapping and Management Project developed practical strategies to build community capacity in Aboriginal Cultural Heritage Management and Protection. The educational programme developed supported learners to use technologies in cultural heritage management. Data were collected using community‐developed fields for inclusion and culturally appropriate encryption of data. Acknowledgements : The authors acknowledge the generous support of Wadawurrung community in the Wadawurrung Dya Baap Ngobeeyt project. The authors pay respects to the elders, families and forebears of the Wadawurrung tribe of the Kulin Nation and acknowledge that the land and waters on which the project was undertaken is the place of age‐old ceremonies of celebration, initiation and renewal.